Lessons from reverse vaccinology for viral vaccine design - Bruno, Luca; Cortese, Mirko; Rappuoli, Rino; Merola, Marcello (Current opinion in virology, 2015)
Although almost 15 years have passed since the birthdate of Reverse Vaccinology (RV), there are very limited applications of this approach to viral vaccines discovery. Undeniably, RV presents a series of advantages as it can virtually identify all potential antigens coded by a genome, irrespective of their abundance, phase of expression and immunogenicity. Additionally, it can be applied to all pathogens, including those that cannot be grown in vitro. In this review we summarize the few examples of RV application to viruses, in particular the Herpesviridae, and report the advantage and limitations of this approach. Next we focus on the novel approaches and additional technologies to vaccine development including structure based approach (Structural Vaccinology [SV]), synthetic biology and some examples of their application in the development of viral vaccines.
Gesehen am 14.10.2020